(untitled) (Mongolian Journal of Arts and Culture, 2023)
This article deals with the analysis and critique of the main statements formulated in the monograph by Professor Ts.Erdenetsog. “Color System of Mongolian Art” as well as an investigation of its basic structure. We proved that this book constitutes an outstanding example of modern Mongolian art history because it provides a broad panorama of the historical evolution of Mongolian artistic tradition since its origins until modern times. Its content is dedicated to the investigation of different questions concerning the formation of the color system in native Mongolian art as well as its further development. Special attention is paid to the extensive study of Mongolian painting of the 20th century when it came into contact with the different traditions of European as well as Russian art. This inevitably resulted in considerable changes in the color system inherent to it. We concluded that the monograph by Professor Erdenetsog has great significance for the further studies of Mongolian art and culture. Монголын урлагт гарсан шинэ номын тойм: Ц.Эрдэнэцогийн Монголын дүрслэх урлаг дахь өнгийн систем номын жишээн дээр